Influence of interest and motivation to learn about student learning outcomes at STAB Dharma Widya in Tangerang City: Influence of interest and motivation to learn about student learning outcomes at STAB Dharma Widya in Tangerang City - Alvin S Purnama; Muljadi (Dhammavicaya, 2021)
ABSTRACT Student learning results are a very important element in achieving the objectives of education. The preliminary survey showed that the student learning outcomes at STAB Dharma Widya is not as expected in fact, therefore the student learning outcomes are interesting to research. This research aims to determine how the student learning outcomes can be improved by researching the influence between students learning outcomes and other variables: their own interests and self-study motivation or collectively. This research is done by quantitatively with the survey method. The population in this study was all active students of STAB Dharma Widya for 89 students. Data is collected through the questionnaire, and analyzed with regression-correlation statistics. bThe results showed that there was a positive influence between the interest and the student learning outcomes with the correlation coefficient ry1 = 0,901, there was a positive relationship between motivation and student learning outcomes with correlation coefficient ry2 = 0,988, there was positive influence of interest and motivation together with student learning outcomes, with correlation coefficient ry12 = 0,991. This suggests that student learning results can be improved through increased interest and motivation to learn both independently and jointly. Key words : Interest, Motivation, Learning Outcomes ABSTRAK Hasil belajar mahasiswa merupakan unsur yang sangat penting dalam pencapaian tujuan Pendidikan. Survei pendahaluan menunjukkan bahwa hasil belajar mahasiswa di STAB Dharma Widya saat ini tidak sesuai dengan yang diharapkan dengan kenyataaan, oleh karena itu hasil belajar mahasiswa menarik untuk diteliti. Penelitian ini bertujuan untuk mengetahui bagaimana hasil belajar mahasiswa itu dapat ditingkatkan dengan cara meneliti pengaruh antara hasil belajar mahasiswa dengan variabel lain yaitu minat dan motivasi belajar secara sendiri-sendiri maupun secara bersama-sama. Penelitian ini dilakukan dengan secara kuantitatif dengan metode survey. Populasi dalam penelitian ini adalah seluruh mahasiswa aktif Sekolah Tinggi Agama Budha Dharma Widya sejumlah 89 mahasiswa. Data dikumpulkan melalui kuisioner, dan dianalisis dengan statistik regresi- korelasi. Hasil penelitian menunjukkan bahwa terdapat pengaruh positif antara minat dengan hasil belajar mahasiswa dengan koefisien korelasi ry1=0,901, terdapat hubungan positif antara motivasi dengan hasil belajar mahasiswa dengan koefisien korelasi ry2=0,988, terdapat pengaruh yang positif minat dan motivasi secara bersama-sama dengan hasil belajar mahasiswa, dengan koefisien korelasi ry12=0,991. Hal ini menunjukkan bahwa hasil belajar mahasiswa dapat ditingkatkan melalui peningkatan minat dan motivasi belajar baik secara sendiri - sendiri maupun secara bersama-sama. Kata kunci : Minat, Motivasi, Hasil belajar